커튼원양해파리 Chrysaora pacifica (Goette, 1886) (Semaeostomeae; Pelagiidae)의 분자 마커를 이용한 한국내 지리적 분포 - 서요셉; 김대현; 채진호; 기장서; Seo, Yoseph; Kim, Dae-Hyun; Chae, Jinho; Ki, Jang-Seu (Ocean and polar research, 2020)
The distribution and genotypes of the sea nettle Chrysaora pacifica have been reported in the South Sea of Korea; however, little research work has been attempted in the East Sea. Here, we collected similar jellyfishes from the East Sea coasts (Goseong, Yangyang and Sokcho), and identified them to the sea nettle morphologically. In addition, the genotypes of these sea nettle were compared with those from the South Sea (Tongyeong and Geoje). Phylogenetic analysis by using the mitochondrial COI sequences showed that the genus Chrysaora was clearly separated from other taxa to be formed a monophyletic group, with each species distinctly separated. C. pacifica in the East and South Seas was separated geographically by the COI phylogeography, representing potentially different populations. The COI gene of the Korean C. pacifica had approximately 7 times more genetic variation than the nuclear ITS rDNA, and thus it might be considered as a useful marker for genetic analysis of the jellyfish population.